Definición de dosis de nitrógeno, fósforo y potasio para una máxima producción del maíz híbrido Advanta 9313 mediante el diseño central compuesto - Gavilánez Luna, Freddy Carlos; Gómez Vargas, María José (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2022)
The absence of knowledge regarding the intervals of macro-nutrients such as nitrogen (N), phosphorus (P) and potassium (K) applied to corn is one of the flaws that do not allow us to take advantage of the potential of certified seeds, which is complicated even more so when the appropriate experimental designs are not used to establish the said intervals. Faced with this situation, this trial was developed with an incomplete second-order factorial arrangement called central compound design (DCC), in order to identify macro-nutrient intervals for greater corn production. A randomized complete block distribution was used in which 15 formulations (treatments) of N-P-K were tested with three repetitions of each one and the dry grain yield was evaluated as a response variable. The data were evaluated by means of analysis of variance to detect linear and quadratic effects, the respective response surfaces and contour graphs were obtained and a second order model was fitted. It was found that the highest corn yields, between 10 to 11 t/ha, were obtained when applying between 110 to 140 kg/ha of nitrogen, from 50 to 70 kg/ha of phosphorus and from 100 to 140 kg/ha of potassium; in addition to corroborating the goodness of the DCC when the limits of experimental operation of the study factors are known.